Engineering aspects of herbal and phytochemical processing: A Malaysian perspective - Ramlan, Abdul Aziz, Prof.; Mohamad Roji, Sarmidi, Prof. Dr.; Sivakumar, Kumaresan; Chwan, Dominic Yee Foo (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s homepage at http://www.myiem.org.my/